Peran Bimbingan dan Konseling Pendidikan Islam dalam Meningkatkan Partisipasi dan Kreativitas Siswa pada Lomba Gebyar Muharram Tinggat SD di Desa Sugaring Bayu, Kecamatan Bandar, Kabupaten Simalungun - Uswatun Hasanah; Azsyura Safitri; Ali Daud Husad (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the role of Islamic Educational Guidance and Counseling in enhancing student participation and creativity in the Gebyar Muharram competition at the elementary school level in Sugarang Bayu Village, Bandar District, Simalungun Regency. This research employs a field research method with a descriptive qualitative approach, allowing the researcher to explore information in depth through direct observation and interviews with key informants such as the village head, students, and other related parties. The results reveal that Islamic Educational Guidance and Counseling plays a significant role in increasing student participation through approaches that involve motivation, confidence building, and exploring students' potential. This activity not only encourages student involvement in the competition but also has a positive impact on their character, such as fostering courage, self-confidence, and enthusiasm for learning. The guidance strategies applied, including group discussions (FGD), problem-solving activities, and creative task assignments, have proven effective in developing student creativity. Moreover, collaboration with the community and parents in skill training has further strengthened the relationship between the school, family, and community. This study concludes that the role of Islamic Educational Guidance and Counseling not only enhances student participation in competitions but also positively influences the holistic development of their character and skills. The findings highlight the importance of active involvement from counselors, teachers, and the community in creating a supportive and enjoyable Islamic learning environment.